Les prés dans les sociétés rétro-littorales : l’exemple de la Blanchardais (Vue, Loire-Atlantique) au xve siècle - Brice Rabot (VertigO, 2022)
Historical sources dealing with the breeding and exploitation of swamps in the Southern part of Brittany at the end of the Middle Ages remain few and so limited to study it shrewdly. This is at least a reason for the lack of interest of historians. Open-minded approaches to other academic matters, first of all geography, allow us to ask further questions such as relationships between territories and rural societies. How did landlords and tenants enhance delicate areas, regularly subject to flooding? How did they trade productions on local or foreign territories? How did the irrigate fields affect the social and rural organization? Has the proximity of the coastline and tide had a significant impact on these territories? This is the first purpose of this paper, beginning with historical sources: the accounting series of the seigniory of La Blanchardais (located in Vue, Loire-Atlantique). The proximity of major links undoubtedly helps trade along. Further aspects will be taken into account in this note, by crossing references altogether.